Driving Innovation and Competitive Advantage through Human Resource Management, Culture, Technology, and Employee Comitment - Anung Haryanto; Sonya Sidjabat; Devi Marlita; Mochamad Ramza Rapier Gussa; Pipit Sundari (Penerbit Goodwood, 2026)
Purpose: This study examines how organisational culture, employee commitment and Human Resource Management (HRM) practices jointly influence innovation and competitive advantage.Research Methodology: A quantitative survey design was adopted, and data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test direct and indirect relationships among human resouce management, culture, technology, and employee commitment on innocation and competitive advantage.Results: Results reveal that culture significantly affects HRM practices, innovation and competitive advantage, HRM practices are strong predictors of both innovation and competitive advantage, employee commitment has a direct effect on competitive advantage but not on HRM or innovation, and HRM mediates the relationship between culture and both innovation and competitive advantage, but not for employee commitment.Conclusions: The findings indicate that culture and HRM form the core mechanisms driving innovation capability and competitive outcomes, while employee commitment plays a more limited role unless embedded in a strong cultural?HRM system.Limitations: This study uses a cross-sectional design and self-reported data, which may limit causal interpretation and generalizability.Contributions: The study contributes to theory by clarifying the mechanism through which culture converts into performance via HRM and innovation. It offers practical guidance for aligning culture, HRM practices and innovation strategy.